Social Business Strategy Analysis of Canvas Model (SBMC) Souvenir Bamboo Tasik (Sobat Asik) in Pandemic Time - Pebriani, Ayu; Nurfitriya, Mira; Koeswandi, Tika Annisa Lestari (A Social Science and Entrepreneurship Journal, 2023)
Study this background by the Covid 19 pandemic in Indonesia which caused problem are you serious appear like decrease in sales volume good for company big as well as SMEs such as Bamboo Souvenirs Lake (Sobat Asik) in the city of Tasikmalaya. Formulas problem in study this is the sales volume of Bamboo Souvenirs Lake (Sobat Asik) in time Covid-19 pandemic is decreasing as well as no balanced with marketing optimally. The Purpose for knowing how description general and form strategy business Social Business Model Canvas (SBMC) Bamboo Souvenir Lake (Sobat Asik) and how formulation the right strategy at the time Covid-19 pandemic. Method study use method qualitative descriptive. Primary data obtained from company internal party buddy Absorbed while secondary data obtained from multiple data books, journals and bulletin. Results the research is strategy social business model canvas (SBMC) can made tool analysis new for social enterprise, which aims for designing formulation strategy business new and analyzed with strategy blue ocean for knowing scale priority strategy formulated business.